Analisis Dampak Gaya Kepemimpinan dan Budaya Kerja terhadap Kinerja Karyawan (Studi Kasus: Keperawatan Rs Anggota Hermina Tahun 2015) - Oktapianti Oktapianti; Ignatius Jeffrey (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2017)
Success or failure of a company is determined by the leader. Good leadership in an organization is, supposed to be, also supported by the work culture of the employees in that company. The stronger the leadership style applied and supported by the implementation of good work culture, can improve the performance of employees, and ultimately the achievement of the company. The aim of this research is to analyze the impact of leadership style and work culture on employee performance in the field of nursing at Hermina Hospital members. The variable in this research is transformational leadership style (X1) and work culture (X2), as well as employee performance (Y). Samples used as many as 173 respondents from 21 Hermina Hospital members with census techniques. Data is collected using questionnaires, then analyzed by using multiple linear regression statistical methods. The Results showed there were a positive influence of leadership style on employee performance and positive influence of work culture on employee performance. However, compared to the amount of work culture, the style of leadership has a greater influence on performance, with the influence score of 30.6 %.